2022
DOI: 10.1007/s11010-022-04394-4
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: contribution of inflammatory and genetic factors

Abstract: Retinopathy of prematurity (ROP) is a retinal vasoproliferative disorder that represents an important cause of childhood visual impairment and blindness. Although oxidative stress has long been implicated in ROP etiology, other prenatal and perinatal factors are also involved. This review focuses on current research involving inflammation and genetic factors in the pathogenesis of ROP. Increasing evidence suggests that perinatal inflammation or infection contributes to ROP pathogenesis. Cytokines and chemokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 182 publications
0
15
0
Order By: Relevance
“…Microglial cells play active roles in maintaining the normal structure and functioning of the retina. In a chronic pre-inflammatory environment, microglia become pathologically activated and release excessive inflammatory mediators that promote retina damage and disease progression [43][44][45][46] . Preventing chronic microglial activation by GSDMD-KO would certainly reduce retina injury and progression of ROP caused by chronic hyperoxia exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Microglial cells play active roles in maintaining the normal structure and functioning of the retina. In a chronic pre-inflammatory environment, microglia become pathologically activated and release excessive inflammatory mediators that promote retina damage and disease progression [43][44][45][46] . Preventing chronic microglial activation by GSDMD-KO would certainly reduce retina injury and progression of ROP caused by chronic hyperoxia exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Using GO analysis, we found that the host genes of the down-regulated circRNAs were enriched in oxygen transport and binding. ROP is induced by hypoxia leading to pathological neovascularization, and oxygen plays an important role in the pathogenesis of ROP ( 36 ). An in vivo study indicated that hyperoxia treatment is a useful therapeutic strategy in targeting pathological neovascularization in ischemic retinopathy, and does not have the inflammatory effect related to anti-VEGF therapies ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ceRNA regulatory network constructed in the current study identified numerous miRNAs and target genes, and GO and KEGG analyses identified key biological processes such as “regulation of cytokine secretion”. Many cytokines, such as IL-12, IL-17 and IL-23 have been found to have fundamental roles in ocular angiogenesis and ROP pathogenesis ( 36 , 41 43 ). Therefore, the present results of bioinformatics analysis are consistent with previous findings, and indicate that circRNAs may play a regulatory role in the effect of cytokines on angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated heritability for susceptibility to ROP has been reported to be approximately 70–73% [ 410 , 411 ]. Several candidate genes modulating downstream inflammatory and angiogenic pathways leading to ROP have been identified [ 413 ] and may potentially become targets of novel therapeutics.…”
Section: Novel Pharmacological Agents Linking To Cytokine Signaling P...mentioning
confidence: 99%